Impact of neuromuscular control exercises on passing skills and agility improvement in executing rolling skills among youth soccer players - Khraibet, R. M. (Trends in Sport Sciences, 2025)
Introduction: Neuromotor exercises, which enhance motor control and muscular coordination, play a crucial role in optimizing the performance of soccer players, particularly in skills such as passing and dribbling. These exercises are designed to improve neuromuscular fitness that is vital for executing complex movements with precision and agility on a soccer field.